Development of English Vocabulary Learning Media Based on Word Connect Game Application: A Research and Development Study - Daud, Enni Akhmad; Nirmala Sinta, Meilan; Laade, Salman (Al-Lisan: Jurnal Bahasa, 2022)
Language skills must be supported by vocabulary mastery, because vocabulary is the framework of a language. The success of teaching must not only pay attention to the material and learning methods, but also pay attention to the learning media. Nowadays, learning media also follows the development of technology and information with many applications available on the Google playstore and can be accessed using the internet network. This research aims to design a word connect game application which used to improve the students’ vocabulary. This research used research and development design in two step, namely need analysis and design. The result of this research showed that 99% students need word connect game application to improve their vocabulary. There are seven steps in designing word connect game. Therefore, this research concluded that word connect game application can be used as a learning media in improving the students’ vocabulary. This research implies to used word connect game application as a learning media in learning English